(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
This paper looks at a major employment concern among recent college graduates: underemployment. Using a sample of 283 recent business college graduates, the research investigates the consequences of underemployment on people’s perceptions regarding their jobs, professions, and life in general. It also examines how recent college graduates cope with underemployment and how those coping mechanisms affect their mental health. The paper closes with suggestions for further research on underemployment among recent graduates in terms of theory development, research methodology, and public policy making. Indeed, in this research on laid-off individuals, underemployment has nearly always been defined in terms of salary disparities between the current position and the one held before to the layoff. "Current earnings that are at least 20% less than earnings in the preceding job" is the most common definition of underemployment. The underemployment of recent college graduates is examined in this essay, which is a topic that is frequently overlooked. A growing number of young people are finding that graduating from college does not guarantee a full-time job.